Mental health impacts of voluntary and involuntary unemployment among Australians in later working life with and without disability - Yufan Chen; Glenda M Bishop; Alexandra Devine; Karinna Saxby; Kate Mason; Tania King; Anne Kavanagh; Zoe Aitken (Social Psychiatry and Psychiatric Epidemiology, 2026)
Abstract Purpose Employment is a key determinant of mental health, with evidence suggesting greater benefits for people with disability relative to people without disability. However, little is known about how retirement impacts mental health for people with disability. This study examined the mental health effects associated with voluntary and involuntary changes in employment status for adults in later working life and explored differences by disability status. Methods We used 13 waves of data from the Household, Income and Labour Dynamics in Australia Survey, comprising 9,162 adults aged 45–69 years. Employment status was classified as employed, voluntarily unemployed, or involuntarily unemployed. Mental health was measured using the Mental Health Inventory (MHI-5). Effects of employment transitions on mental health were estimated using fixed effects regression models, including interaction terms to explore differential effects for people with persistent disability, fluctuating disability, or no disability. Results For people with persistent and fluctuating disability, both involuntary (persistent: -4.51, 95% CI -6.79, -2.24; fluctuating: -4.98, 95% CI -6.78, -3.19) and voluntary unemployment (persistent: -3.62, 95% CI -5.43, -1.82; fluctuating: -1.26, 95% CI -2.54, 0.01) were associated with poorer mental health compared to employment. For people without disability, only involuntary unemployment was associated with poorer mental health (-2.45, 95% CI -3.80, -0.69). Conclusion Our findings highlight negative mental health effects associated with both voluntary and involuntary unemployment for people with disability, whereas only involuntary unemployment had a negative effect for people without disability. Policy efforts are needed to support people with disability when transitioning out of employment.